2016
DOI: 10.1007/s00394-016-1360-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and vitamin D3 combinations improve fatty liver disease through AMPK-independent mechanisms

Abstract: The results showed high calcium plus VitD intakes considerably prevent biochemical and hepatic changes induced by HFHFr diet, probably via an insulin and AMPK-independent pathway. A low intake of these two nutrients was also linked with a significant decrease in HFHFr diet-induced hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
3
8
1
Order By: Relevance
“…Thus, the inverse association might partly be explained by increased whole-body fat oxidation rates. Fourth, an animal study found that calcium and vitamin D combinations could prevent NAFLD development [37]. Finally, yogurt is seen as a nutrient-dense food linked with healthy diet habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inverse association might partly be explained by increased whole-body fat oxidation rates. Fourth, an animal study found that calcium and vitamin D combinations could prevent NAFLD development [37]. Finally, yogurt is seen as a nutrient-dense food linked with healthy diet habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium content in American Institute of Nutrition (AIN93) standard mice feed is 0.5%. After referring to other groups and our previous research, we chose 1.2% calcium in our calcium supplementary feed [16,17]. Calcium carbonate was used to regulate calcium content in the calcium supplementation group.…”
Section: Mice and Sample Collectionmentioning
confidence: 99%
“…Previous studies have shown that high Ca and Vitamin D 3 intakes caused lesser adiposity and lipid accumulation, probably via an insulin and AMPK- independent pathway [ 34 ]. However, few studies have reported about the effect of dietary P on the AMPK pathway.…”
Section: Resultsmentioning
confidence: 99%